The Length of Stay Difference between Under 5 Years Patient with Acute Diarrhoea Treated With and Without Probiotic An Analytical Study in RSUD Kota Semarang during the Period January to December 2007 - F. Riandari, F. Riandari; Priyantini M., Sri (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2011)
Background: Diarrhoea is still public health problem and often cause outbreak with various morbidity and mortality. The long onset of acute diarrhoea causes the length of stay that affect the cost. So proper management is needed to shorten inpatient length of stay. Probiotic can make the convalescence of children with acute diarrhoea faster. The aim of the study is to know the lenght of stay difference between underfive year old children with acute diarrhoea treated with and without probiotic.Design and Methods: The study was an analitical study with case control design. Study Sample were all inpatient 6-24 month old children with acute diarrhoea in Kota semarang Hospital since January – December 2007. Data were obtained from medical record in pediatric unit. Data analysis with stastitical test of Mann Whitney.Results: Of 130 samples, the lenght of stay average of < 5 years old children with acute diarrhoea with probiotik was 3,42 days compare 4,03 days children acute diarrhoea without probiotik. It is concluded that there was a significantly difference between two groups acute diarrhoea with probiotik and without probiotik.Conclusion: There was a significant difference between the length of stay for the patients with acute diarrhea with and without probiotic treatment. Mean of the length of stay for under 5 years old baby with and without probiotic were 3.42 days and 4.03 days respectively (Sains Medika, 3(1):78-83).